Algebra in the Stone-Cech Compactification : Theory and Applications. - Hindman, Neil (De Gruyter textbook., 2011)
This book, now in its second revised and extended edition, is a self-contained exposition of the theory of compact right semigroupsfor discrete semigroups and the algebraic properties of these objects. The methods applied in the book constitute a mosaic of infinite combinatorics, algebra and topology. The reader will find numerous combinatorial applications of the theory, including the central sets theorem, partition regularity of matrices, multidimensional Ramsey theory, and many more.